Advances in graphene-based supercapacitor electrodes. (November 2020) - Bokhari, Syeda Wishal; Siddique, Ahmad Hassan; Sherrell, Peter C.; Yue, Xiaoyu; Karumbaiah, Kariappa Maletira; Wei, Shanghai; Ellis, Amanda V.; Gao, Wei
Abstract: Graphene-based materials are widely explored as the active electrode materials for energy storage and conversion devices, especially supercapacitors (SCs). Their high electrochemically active surface area, hierarchical porous structure, excellent compressibility, and high mechanical stability, as well as excellent conductivity, are the critical merits for providing robust and facilitative channels for charge transport. Various studies have explored many possible ways to utilize the maximum potential of graphene-based SC electrodes, and graphene research is booming, given its exceptional charge storage properties. This review focuses on the class-specific electrode materials for different types of SCs, followed by the classification and critical review of graphene-based electrodes reported in the past five years. The current challenges in the field have also been discussed with a focus on promising pathways for future research. Graphical abstract: